A institucionalização de práticas intra-empreendedoras em empresas de tecnologia da informação (TI) - Carneiro, José Guilherme Said Pierre (2012)
In many business sectors, organizations have increasingly adopted intrapreneur practices in search of innovation. However, such practices do not always become systematic. The goal of this study is to understand how the institutionalization process of intra-intrapreneurial practices occurs in information technology (IT) companies in the state of Ceará. Understanding intrapreneurship refers to the elements of entrepreneurship and innovation, which are discussed within organizations that produce products and IT services, emerging as engines of a new economy based on technology and knowledge. This understanding becomes of great relevance to the literature in management, as it demonstrates the importance for organizations to invest in processes that allow the increasing occurrence of intra-entrepreneurial practices and innovation. In the study, the theoretical concepts related to intrapreneurship (Pinchot, 1999), entrepreneurship (Drucker, 1986), innovation (Schumpeter, 1982), technology (Roberts; Grabowski, 2004) and the contributions of institutional theory, with the model theoretical Tolbert and Zucker (1999) were used as a basis for identifying the stage of solidification of innovative structures and practices within organizations. This research is exploratory, descriptive, and qualitative. It was carried out through a field survey, with the most representative companies in the IT sector in Ceará. To obtain the data, a structured questionnaire with a sample of 43 professionals, using a Likert scale, was applied. And to deepen the understanding, interviews were conducted with seven managers of the companies comprising the sample. The questionnaire data were analyzed using descriptive statistics of some elements. For the analysis of data from the interviews, content analysis was used, and the division of categories was based on the literature review. The results demonstrated the existence of several intra-entrepreneurial practices in the organizational field researched, some more planned and systematic in certain companies. The active factors in the three stages of institutionalization were also checked and there are similarities in the structures adopted by organizations, there is evidence of a positive relationship between the adoption of structures that encourage innovation and the final results.